A case of varicella induced remission of nephrotic syndrome - Joshi, Amey; K., Subramanya N.; G., Muralidhar (International Journal of Contemporary Pediatrics, 2020)
Here authors report a case of a 7-year old girl diagnosed with nephrotic syndrome with urinary tract co-infection who during treatment with steroids developed a Varicella Zoster infection. After cessation of steroid therapy and commencement with antiviral drugs, the patient showed significant reduction in nephrotic features and complete resolution of nephrotic syndrome as with the VZV super-infection.